Analysis of Factors That Influence Civil Servants Performance in Balai Perikanan Budidaya Air Payau (BPBAP) Situbondo - Puryantoro Puryantoro; Hasbiadi Hasbiadi; Doddy Ismunandar Bahari (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2020)
Balai Perikanan Budidaya Air Payau Situbondo (BPBAP) is one of the largest centres in East Java, to be precise in Situbondo Regency. BPBAP is a government- fish centre that is well developed as an engineering centre. The institution's performance resulted from the performance of employees that develop every year. To analyze the performance of BPBAP employees, this research was compiled regarding the factors that influence it. The research design used was survey research, with a total of 88 respondents. The analysis method used is multiple linear regression analysis including, t-test, F test, and coefficient. The results showed that the variables of transformational leadership style, transactional leadership style, organizational culture and motivation which had a correlation of 0.708 to performance of BPBAP employees which was a strong relationship. Furthermore, partially the transformational leadership style variable has a significant effect on performance, the transactional leadership style variable has no significant effect on performance, the organizational culture variable has a significant effect on performance and the work motivation variable has a significant effect on performance. The independent simultaneous variable has a significant effect on the dependent variable.Balai Perikanan Budidaya Air Payau Situbondo (BPBAP) is one of the largest centres in East Java, to be precise in Situbondo Regency. BPBAP is a government- fish centre that is well developed as an engineering centre. The institution's performance resulted from the performance of employees that develop every year. To analyze the performance of BPBAP employees, this research was compiled regarding the factors that influence it. The research design used was survey research, with a total of 88 respondents. The analysis method used is multiple linear regression analysis including, t-test, F test, and coefficient. The results showed that the variables of transformational leadership style, transactional leadership style, organizational culture and motivation which had a correlation of 0.708 to performance of BPBAP employees which was a strong relationship. Furthermore, partially the transformational leadership style variable has a significant effect on performance, the transactional leadership style variable has no significant effect on performance, the organizational culture variable has a significant effect on performance and the work motivation variable has a significant effect on performance. The independent simultaneous variable has a significant effect on the dependent variable.